Social Transformation in the Northern Coastal Cities of Java: a Comparative Study in Cirebon and Gresik - Riwanto Tirtosudarmo (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2010)
-